Comparative localization of the courses of superficial veins in rabbits' limbs using latex and VeinViewer systems - Karaavci, Funda Aksunger; Karan, Meryem (Wiley, 2023)
The purpose of this study; It is to reveal whether the veinviewer device, which we have not encountered in animals, can be visualized in rabbits for thoracic and pelvic limb superficial veins. Therefore, the latex method was used as a gold test to verify VeinViewer precision. For this purpose, the project was designed with two stages. In the first stage, the extremities of 15 New Zealand white rabbits were imaged using the VeinViewer device, and the results were recorded. In the second stage, the latex injection method was applied to the same animals, the cadavers were dissected, and the obtained results were comparatively analysed. In the rabbits, it was determined that v. cephalica originated from v. jugularis or v. brachialis in the proximity of the insertion of m. omotransversarius and anastomosed with v. mediana at the middle 1/3 level of the antebrachium. It was found that the superficial venous circulation of the pelvic limbs was provided by the branches of v. iliaca externa and v. iliaca interna. The vena saphena medialis was determined to be present in pairs in 80% of the cadavers. All cadavers showed the presence of the ramus anastomoticus cum vena saphena mediali. Additionally, the superficial veins of both the thoracic limbs and pelvic limbs of the rabbits were imaged with the VeinViewer device, which provided results parallel with the results of the latex injection method. Considering that the findings obtained with the latex injection method and the VeinViewer device were compatible, the usage of this device can potentially be considered as an alternative to visualizing superficial veins in animals. Further morphological and clinical studies can prove that the method is applicable.
Keywords: anatomy; latex; near infrared; rabbit; superficial vein; VeinViewer